Masked primes evoke partial responses. Issue 6 (June 2018) - McBride, Jennifer; Sumner, Petroc; Husain, Masud
Backward-masked primes presented outside conscious awareness can affect responses to subsequently presented target stimuli. Differences in response times have been used to infer a pattern of sub-threshold activation and subsequent inhibition of motor plans associated with the primes. However, it is unclear whether competition between alternative responses is fully resolved in the brain or whether activated responses can begin being executed before the final decision to act has been made. Here, we investigate the dynamics of responses evoked by masked primes using a continuous measure – voltage change in force-sensing resistors simultaneously in both hands. Masked primes produced the predicted pattern of motor activation and subsequent inhibition of the primed response. There is no evidence that the effects of masked primes interact with spatial compatibility (e.g., Simon) effects, suggesting separate mechanisms underpinning these effects. Moreover, masked primes evoked partial motor decisions – measurable at the effectors as small amounts of erroneous response – which were usually rapidly corrected. Together, these errors and fast corrections question the 'sub-threshold' nature of responses evoked by masked primes and provide important constraints on models of decision-making.